The Politics and Management of Agencies - Guy B. PETERS (Transylvanian Review of Administrative Sciences, 2011)
The countries of Central and Eastern Europe have not been immune to the appeal of the agency model, and this approach to public governance has now been widely diffused among these countries. These reforms, like all others, must be institutionalized to be effective and the autonomy created by agencies may require subsequent reforms. This introductory article describes the agency approach within the contest of Central and Eastern Europe, and discusses the political and administrative consequences of these reforms.